2023
DOI: 10.1002/cbic.202300008
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Synthetic Biology of Fungi and Contributions to the Discovery of New Molecules

Abstract: The sequencing of fungal genomes is becoming increasingly accessible, with a wealth of data already available. In parallel, the prediction of the putative biosynthetic pathways responsible for the synthesis of potential new natural products is also increasing. The difficulty of translating computational analyses into available compounds is becoming evident, slowing down a process that was thought to be faster with the advent of the genomic era. Advances in gene techniques made it possible to genetically modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…Several studies have shown that biosynthetic gene clusters can be randomly activated by modifying the expression of signaling pathways, cell wall structures, and stress response elements using synthetic biology strategies. In the future, based on a deeper understanding of the gene-splicing mechanism, we can study and develop synthetic components that can be effectively used in multi-gene expression systems, construct efficient chassis that can be easily modified and screened in high throughput [112], and realize the synthesis of large quantities of target active molecules and their derivatives from edible fungus sources. The efficient degradation of SMS could be realized to significantly contribute to the healthy development of the edible fungus industry under the goal of "carbon neutrality" and the creation of a high-economic-value industry.…”
Section: Synthetic Biologymentioning
confidence: 99%
“…Several studies have shown that biosynthetic gene clusters can be randomly activated by modifying the expression of signaling pathways, cell wall structures, and stress response elements using synthetic biology strategies. In the future, based on a deeper understanding of the gene-splicing mechanism, we can study and develop synthetic components that can be effectively used in multi-gene expression systems, construct efficient chassis that can be easily modified and screened in high throughput [112], and realize the synthesis of large quantities of target active molecules and their derivatives from edible fungus sources. The efficient degradation of SMS could be realized to significantly contribute to the healthy development of the edible fungus industry under the goal of "carbon neutrality" and the creation of a high-economic-value industry.…”
Section: Synthetic Biologymentioning
confidence: 99%